2021
DOI: 10.1515/jpm-2021-0181
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression during pregnancy in the era of COVID-19

Abstract: Objectives This study aimed to evaluate anxiety and depression in pregnant women during this global disease. Methods This was a cross-sectional study recruiting 120 pregnant women. The study was conducted at the outpatient clinic of a tertiary hospital. We recruited women attending for antenatal care. Anxiety was evaluated using an Arabic validated Kuwait University Anxiety Scale (KUAS). Depression was evaluated using a valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
1
21
0
1
Order By: Relevance
“…A study conducted by Yan et al [87] (that included 23 studies with 20.569 participants) also found that the prevalence of depression in pregnant and postpartum women was high during the COVID-19 pandemic. Fears of contracting or transmitting COVID-19, worry about their pregnancy and the health of their newborn, the lockdowns/quarantine, poor economic conditions, loss of income, insufficient social support, and lack of access to healthcare professionals contributed significantly to the mental health of pregnant and postpartum women during the COVID-19 pandemic [28,29,35,40]. 8 During the COVID-19 pandemic, meeting the mental health needs of pregnant and postpartum women was a considerable challenge.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Yan et al [87] (that included 23 studies with 20.569 participants) also found that the prevalence of depression in pregnant and postpartum women was high during the COVID-19 pandemic. Fears of contracting or transmitting COVID-19, worry about their pregnancy and the health of their newborn, the lockdowns/quarantine, poor economic conditions, loss of income, insufficient social support, and lack of access to healthcare professionals contributed significantly to the mental health of pregnant and postpartum women during the COVID-19 pandemic [28,29,35,40]. 8 During the COVID-19 pandemic, meeting the mental health needs of pregnant and postpartum women was a considerable challenge.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is comparable to the regional and international studies during the pandemic, who used EPDS. For example, 44.2% of Egyptian pregnant women [24] and 45.9% of Chinese pregnant women were having depressive symptoms during the COVID-19 outbreak [25]. However, research in Greece reports that antenatal depression remained at 13.5% during the pandemic [26].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings should be interpreted with caution as they could be influenced by the sampling and survey techniques used (snowballing and Google Forms): the topic needs to be monitored after the pandemic has receded. It is helpful to note that recent other studies reported different percentages of depressive symptoms: China 45.9% [25], Greece 13.5% [26], Egypt 44.2% [24].…”
Section: Plos Global Public Healthmentioning
confidence: 95%
See 2 more Smart Citations